Red ruby glass from gold nanoparticles obtained by LASiS – a new approach - Almeida, J. C. (2020)
Currently, most of the red colored glasses are still produced using cadmium sulfoselenide, despite its high toxicity. Alternative solutions, more environmentally friendly, have been sought, most of them going through the use of gold or copper nanoparticle, the color being obtained by striking. This work presents a new methodology for production of a red colored glass by the incorporation of gold nanoparticles in the melt, trying to take advantage of an amorphous silica layer involving the nanoparticles. Gold nanoparticles (AuNP) were produced by laser ablation synthesis in solution (LASiS), using a solution of tetraethyl orthosilicate (TEOS) and isopropanol (IPA). A xerogel was prepared using the TEOS:IPA:AuNp suspension, mixed with a alkaline-earth aluminosilicate colorless glass and melted at 1350 °C producing a glass with an intense and homogeneous ruby red color without the need of a striking stage.